Analysis of the Application of Accounting Information Systems in the Revenue and Cash Receipts Cycle (Case Study of the Company PT. ASM) - Nurcahyani, Avilda Regita; Fambudi, Imam Nurcahyo (Jurnal Ekonomi dan Bisnis Digital, 2024)
PT. ASM is a research, development and consulting services company that has the main objective of assisting in the implementation of Domestic Component Level (TKDN) certification for a product. This study aims to determine how the application of accounting information systems related to the revenue and cash receipt cycle before and after PT ASM uses web-based applications in order processing, and measuring the effectiveness. This study uses a descriptive qualitative approach with a case study research type. The results of the study indicate that web-based applications as one of the improvements to accounting information systems that have been effectively implemented to minimize obstacles in order processing, but have not been fully effective in reducing the overall order completion time significantly.